Development of real-time PCR tests for the detection of Tenebrio molitor in food and feed. Issue 8 (3rd August 2017) - Debode, Frédéric; Marien, Aline; Gérard, Amaury; Francis, Frédéric; Fumière, Olivier; Berben, Gilbert
ABSTRACT: Insects are rich in proteins and could be an alternative source of proteins to feed animals and humans. Numerous companies have started the production of insects for feed purposes. In Europe, these processed animal proteins are not yet authorised by legislation as many questions still need to be answered concerning this 'novel food'. Authorisations will be possible when methods of authentication of the products are available. In this study we propose real-time PCR methods for the specific detection of the mealworm ( Tenebriomolitor ), one of the most widely used insects for food and feed production. Two PCR assays are proposed: the first based on the wingless gene and the second based on the cadherin gene. The PCR tests amplify fragments of 87 bp. These qualitative methods were tested according to several performance criteria. The specificity was tested on 34 insect species' DNA, but also on non-insect species including crustacean, mammals, birds and plants. The limit of detection was determined and was below 20 copies for the two PCR tests. The applicability of the tests was demonstrated by the analysis of real-life processed samples containing T . molitor .